(untitled) (International Journal of Engineering and Computer Science, 2017)
In most of the Universities, results are published on web or send via PDF files. Currently many of the colleges use manual process to analyze the results. Sadly the college staff has to manually fill the student result details and then analyze the rankings accordingly. Our proposed system will extract the data automatically from PDF and web, create dynamic database and analyze data, for this system make use of PDF Extractor, Pattern matching techniques, data mining, Web mining technique and sorting technique.